Circularly Polarized Microstrip Yagi Array Antenna with Wide Beamwidth and High Front-to-Back Ratio - Yun Hao; Haomeng Tong; Xihong Ye (International Journal of Antennas and Propagation)
A circularly polarized (CP) Microstrip Yagi array antenna (MSYA) is designed in order to achieve high front-to-back ratio R(F/B) and high gain over wide range in the forward radiation space. A Wilkinson power divider owning two output ways with the same magnitude and different phase is used to feed the antenna. Parametric studies are carried out to investigate the effects of some key geometrical sizes on the antenna’s performance. A prototype of the antenna is fabricated, and good agreement between the measured results and the numerical simulations is observed. The overlap bandwidth of VSWR ≤ 1.5 and AR ≤ 3 dB is about 11%. The steering angle (α) between the peak gain direction and the broadside can achieve 35°, R(F/B) reaches 19 dB, and the gain at the front point (G0) is only 4.3 dB lower than the maximum gain (Gm). The antenna has a wide beamwidth CP radiation pattern over wide spatial range including 0° ≤ θ ≤ 90° in vertical plane and −35° ≤ φ ≤ 55° in horizontal plane.